2021
DOI: 10.3390/ijms22168600
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Allicin Associated with Fibrosis in Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is characterized by pulmonary vascular remodeling. Recent evidence supports that inflammation plays a key role in triggering and maintaining pulmonary vascular remodeling. Recent studies have shown that garlic extract has protective effects in PAH, but the precise role of allicin, a compound derived from garlic, is unknown. Thus, we used allicin to evaluate its effects on inflammation and fibrosis in PAH. Male Wistar rats were divided into three groups: control (CON), mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…Furthermore, we also summarized the natural products involved in all mechanisms. Many of these natural products, such as TIIA, MLB, resveratrol, ligustrazine, astragaloside IV, baicalin, baicalein, betaine, and allicin, may act by reducing the inflammatory response [ 38 , 45 , 50 , 60 , 69 , 72 , 90 , 107 , 114 , 115 ]. MLB, SAA, ligustrazine, resveratrol, 18β-glycyrrhetinic, wogonin, and genistein ameliorate oxidative stress [ 42 , 43 , 129 , 131 , 132 , 134 , 162 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we also summarized the natural products involved in all mechanisms. Many of these natural products, such as TIIA, MLB, resveratrol, ligustrazine, astragaloside IV, baicalin, baicalein, betaine, and allicin, may act by reducing the inflammatory response [ 38 , 45 , 50 , 60 , 69 , 72 , 90 , 107 , 114 , 115 ]. MLB, SAA, ligustrazine, resveratrol, 18β-glycyrrhetinic, wogonin, and genistein ameliorate oxidative stress [ 42 , 43 , 129 , 131 , 132 , 134 , 162 ].…”
Section: Discussionmentioning
confidence: 99%
“…PVR is often accompanied by an increased expression of inflammatory factors such as TNF-α, IL-6, and IL-1β [ 113 ]. Resveratrol, puerarin, allicin, grape seed proanthocyanidin, and many other natural products can inhibit lung inflammation by reducing the expression of inflammatory factors such as TNF-α, IL-6, and IL-1β in the lung, thereby reducing pulmonary vasoconstriction and vascular remodeling [ 59 , 79 , 114 , 115 ]. Notably, some studies have indicated that IL-6 is one of the most important inflammatory cytokines in the development of PH [ 116 , 117 ].…”
Section: Mechanism Of Natural Products For the Treatment Of Phmentioning
confidence: 99%
“…TGF-β pathways may therefore be beneficial as a therapeutic target. For example, treatment with allicin—derived from garlic—prevented RV fibrosis in rat models of pulmonary arterial hypertension ( 28 ). Neurohormones, such as aldosterone, angiotensin II, epinephrine, and norepinephrine, also activate cardiac myofibroblasts and stimulate collagen production ( 29 , 30 ).…”
Section: Mechanisms Of Systemic Right Ventricle Failurementioning
confidence: 99%
“…40 Sanchez et al studied the anti-inflammatory effect of allicin on fibrosis in pulmonary hypertension. 41 They found that allicin inhibited the expression of interleukin-6 (IL-6), IL-1β, TNF-α, and macrophage marker (Cd68) and inhibited the activation of the NF-κB signaling pathway. Moreover, the circulating form of allicin (S-allylmercaptoglutathione, GSSA) in the in vivo system stimulated immunoglobulin secretion by binding to the scavenger receptor class B type 1 (SCARB 1) of CD 19 + B lymphocytes, which revealed an immunostimulatory effect of allicin.…”
Section: ■ Bioavailability and Metabolismmentioning
confidence: 99%